2023
DOI: 10.1186/s12859-023-05134-1
|View full text |Cite
|
Sign up to set email alerts
|

A signature of immune-related genes correlating with clinical prognosis and immune microenvironment in sepsis

Abstract: Background Immune-related genes (IRGs) remain poorly understood in their function in the onset and progression of sepsis. Methods GSE65682 was obtained from the Gene Expression Omnibus database. The IRGs associated with survival were screened for subsequent modeling using univariate Cox regression analysis and least absolute shrinkage and selection operator in the training cohort. Then, we assessed the reliability of the 7 IRGs signature's indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Immunosuppression, particularly post-clinical 'recovery,' has been identified as a crucial factor [ [10] , [11] , [12] , [13] ]. Previous evidence has demonstrated that analyzing the differential expression of immune-related genes (IRGs) in sepsis aids in identifying biomarkers for early prediction and diagnosis [ [14] , [15] , [16] , [17] , [18] ]. Therefore, IRGs hold promise as potential biomarkers for predicting and treating sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression, particularly post-clinical 'recovery,' has been identified as a crucial factor [ [10] , [11] , [12] , [13] ]. Previous evidence has demonstrated that analyzing the differential expression of immune-related genes (IRGs) in sepsis aids in identifying biomarkers for early prediction and diagnosis [ [14] , [15] , [16] , [17] , [18] ]. Therefore, IRGs hold promise as potential biomarkers for predicting and treating sepsis.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Another work has shown that the infiltration of inflammatory cells and the release of pro-inflammatory mediators play a significant role in ALI development. 10 Macrophages, as the first line of defense of lung immune defense, are broadly distributed on the surface of airways and alveoli. Macrophages play vital roles in ALI via cytokines and chemokines release.…”
Section: Introductionmentioning
confidence: 99%